Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3892/ol.2018.7969
|View full text |Cite
|
Sign up to set email alerts
|

In�silico analysis identifies CRISP3 as a potential peripheral blood biomarker for multiple myeloma: From data modeling to validation with RT-PCR

Abstract: Abstract. Octamer-binding protein 2 (Oct2) binds to the ATGCAAAT octamer on the IgH enhancer and stimulates IgH expression in human multiple myeloma (MM). Cysteine-rich secreted protein 3 (CRISP3) possesses the ATGCAAAT sequence and thus is activated by Oct2 in mouse B cells, suggesting that CRISP3 may be activated in and be a potential biomarker for MM. The present study involved a meta-analysis of the gene expression profiling data of human MM peripheral blood. Significantly expressed genes were analyzed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Previously described as upregulated as part of a 7-gene predictive signature of early primary prefibrotic myelofibrosis (prePMF) [ 18 ]. It has also been identified as a potential PB biomarker for multiple myeloma [ 19 ]. Its role in MPNs remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Previously described as upregulated as part of a 7-gene predictive signature of early primary prefibrotic myelofibrosis (prePMF) [ 18 ]. It has also been identified as a potential PB biomarker for multiple myeloma [ 19 ]. Its role in MPNs remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Human CRISP3 is located on human chromosome 6 and is the third member of the cysteine rich secretory protein family and is widely distributed in human tissues. It is detected in human body fluid secretion including sweat, plasma, prostate, pancreas and salivary glands [20]. The study found that CRISP3 is low expressed in colon, thymus, ovary and epididymis tissues, but its specific function has not been clearly studied [21].…”
Section: Discussionmentioning
confidence: 98%
“…CONOR and preprocessCore in the R software package were used to combine the gene expression estimates from different studies [ 15 , 16 ]. During the data-merging process, the Log2-transformed raw intensity estimates were transformed by iterative clustering until convergence to a minimum sum of the Euclidean distance, which has been proven to be an effective means to remove systematic differences between studies while preserving the completeness of the biological information [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%